IMPLIKASI YURIDIS PUTUSAN MAHKAMAH KONSTITUSI NOMOR 91/PUU-XVIII/2020 TERHADAP KEDUDUKAN UU NO. 11 TAHUN 2020 TENTANG CIPTA KERJA - Andini Camelia; Cenlia Brigita Engkolan; Ika Rachmawati Sukarno Putri; Nasywa Laffaiza; Tazkia Tunnafsia Siregar (Media Keadilan: Jurnal Ilmu Hukum, 2023)
Constitutional  Court  Decision  Number:  91/PUU-XVIII/2020  which  granted  the  formal  test  of  Law  Number  11  of  2020  concerning  Job  Creation.  In  fact,  the  Judge's  Decision  is  intended  to  end  disputes  and  differences  in  interpretation  of  a  provision.  However,  this  Decis on  actually  creates  dualism  regarding  the  applicability  of  the  Job  Creation  Law,  because  on  the  one  hand  this  Law  is  declared  unconstitutional,  but  on  the  other  hand  this  Law  remains  in  effect  and  has  binding  legal  force.  This  juridical  issue  will  be  examined  using  normative  legal  research  imethods.  From  ithe  results  of  the  research,  it  was  concluded  that  the  meaning  of  conditional  unconstitutional  in  this  Decision  is  the  establishment  of  Law  no.  11  of  i2020  icontradicts  the  1945  Constitution  or  is  conditionally  (temporary)  unconstitutional.  This  temporary  unconstitutional  status  depends  on  conditions  in  the  form  of  an  obligation  for  legislators  to  make  improvements  to  the  formation  of  Law  no.  11  of  2020  for  ia  period  of  2  (two)  years.  As  for  the  2  (two)  year  period,  the  Job  Creation  Law  will  still  apply  based  on  points  '4'  iand  '6'  in  the  ruling.